Capital structure as a mediating factor in the relationship between uncertainty, CSR, stakeholder interest and financial performance - Ahmed Imran Hunjra; Peter Verhoeven; Qasim Zureigat (Journal of Risk and Financial Management, 2020)
We examine the mediating role of capital structure in the perceived relationship of uncertainty, corporate social responsibility (CSR), stakeholder interest and financial performance. We collect data through questionnaires, and survey the Chief Financial Officers (CFOs) of the service sector of Pakistan. We apply Structure Equation Modeling (SEM) for data analysis. We find that CFOs perceive uncertainty, CSR and stakeholder interest to have both direct and indirect impacts on financial performance. In particular, we find evidence of the mediating effect of capital structure in the relationship. Our findings imply that firms screen out uncertain situations while making capital structure decision and pursuing CSR-related activities.
Keywords: 330; capital structure; uncertainty; CSR; stakeholder interest; financial performance